The Role of Innovation Capability and Gender on Green Public Procurement in Higher Education Institutions - Sulistiani, Dwi; Cholifah, Nur; Hasanah, Siti Ma'rifatul (International Journal of Educational Management and Innovation, 2025)
Background. Higher education institutions (HEIs), as public sector organizations, are required to support the Sustainable Development Goals (SDGs), including the implementation of Green Public Procurement (GPP). This research aims to provide empirical evidence of the moderation effect of gender on the influence of innovation capability on GPP. Methods. This quantitative research used 68 questionnaires, which were filled in by members of the internal auditor unit and procurement officials of Islamic state HEIs. The OLS (Ordinary Least Squares) test was carried out using the Minitab application. Results. The research results show that innovation capability positively affects the implementation of GPP, as long as gender is a moderation variable on that effect in HEIs (Higher Education Institutions). This research supports the RBV (Resource-Based View) theory that each organization needs resources to support its goals. The results of this research have implications for HEIs to increase their ability to innovate and select male procurement officers who can strengthen support for GPP implementation. For regulators, the results of this research can be used as a reference for making regulations regarding the implementation of GPP in HEIs. Conclusions. The limitation of this research lies in the limited number of questionnaires at Islamic state HEIs. Further research can expand the scope of research to all types of HEIs and add other variables that support GPP.